PARKIR HOUSE KEEPING IMPLEMENTATION TO INCREASE SAFETY AWARENESS IN ALL BUSINESS PROCESSES - Sartika Rini (Buletin Utama Teknik, 2019)
This article has two main objectives. The first objective is to implement housekeeping (5S) program as a company culture by improving the safe workplace. The second objective is to increase safety awareness as part of respect for people in the company with better housekeeping would support reliable work flow, increase productivity and personnel satisfaction. 5S began as part of the Toyota Production System (TPS) in early and mid-20th century. The main objective is to increase the value of products and or services for customers by eliminating waste from production processes. Among the most common accident causes in many company are unsafe behavior, unsafe action, and unsafe condition which often relate to poor and tidiness. The aim of the program was to improve order and tidiness and consequently safety performance and to achieve better working environment and to reduce accidents caused by slips, trips and falls (on same level).Keywords: : 5S Program, Safe Workplace, Respect For People, Safety PerformanceThis article has two main objectives. The first objective is to implement housekeeping (5S) program as a company culture by improving the safe workplace. The second objective is to increase safety awareness as part of respect for people in the company with better housekeeping would support reliable work flow, increase productivity and personnel satisfaction. 5S began as part of the Toyota Production System (TPS) in early and mid-20th century. The main objective is to increase the value of products and or services for customers by eliminating waste from production processes. Among the most common accident causes in many company are unsafe behavior, unsafe action, and unsafe condition which often relate to poor and tidiness. The aim of the program was to improve order and tidiness and consequently safety performance and to achieve better working environment and to reduce accidents caused by slips, trips and falls (on same level). Keywords: : 5S Program, Safe Workplace, Respect For People, Safety Performance